Factores criminológicos en el delito de hurto de material bélico militar - Olmos Loachamín, Diego Alexis (2025)
The main objective of this scientific article is to determine the criminological factors in the crime of theft of military war equipment committed by the same personnel in the province of Cotopaxi during the year 2024. A synthetic qualitative approach was employed to achieve this, using a descriptivedocumentary methodology with a bibliographic design. Interviews were conducted with Specialist Professors of Master’s in Criminal Law and Criminology at UNIANDES to obtain truthful information and understand the causes that influenced the commitment of this crime. The crime of theft of military war equipment is stipulated in the Comprehensive Organic Criminal Code, Article 197, which states that any police or military personnel who steal military war equipment such as weapons, ammunition, explosives, or equipment used for police or military purposes will be punished with imprisonment of three to five years. The main outcome of this master's thesis is to identify the criminological factors behind the theft of military war equipment and to seek alternatives to prevent such crimes through the monitoring of military armaments and partial inspections at military forts.